1983
DOI: 10.1063/1.94488
|View full text |Cite
|
Sign up to set email alerts
|

Direct etching of polymeric materials using a XeCl laser

Abstract: The direct etching of polyethylene terephthalate film using a XeCl laser has been investigated and is shown to be consistent with a thermal model for degradation. Microstructure revealed by deep etching suggests the UV laser may prove useful for studying polymeric materials. Polyimide and photoresist film has also been directly etched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(132 citation statements)
references
References 6 publications
2
125
0
5
Order By: Relevance
“…Although the approach described above has been adopted previously to examine pulsed lasers, namely excimer lasers, and has been shown to be a sound approach [16], the technique has also been used to investigate CW lasers [1,17,18]. Moreover, the distinct linearity of the data points shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the approach described above has been adopted previously to examine pulsed lasers, namely excimer lasers, and has been shown to be a sound approach [16], the technique has also been used to investigate CW lasers [1,17,18]. Moreover, the distinct linearity of the data points shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Andrew et al [16] used the method to ascertain the minimum fluence required to etch polymeric materials. Schmidt et al [1] utilised the method to calculate the thermal loading of chlorinated rubber during CO 2 and HPDL treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that (1) takes no account of absorption of incident radiation by the plume of removed material 5 and likely changes in the material's level of absorption as removal progresses. Nonetheless, as the work of Andrew et al [13] and Schmidt et al [14] demonstrated this simple form of the expression is quite adequate as a first approximation. By rearranging (1) in terms of the absorption length, 1/α, thus:…”
Section: Determination Of Absorption Lengthmentioning
confidence: 99%
“…Although this approach has been adopted previously to examine pulsed lasers (excimer) and shown to be sound [13], the technique has also been used to investigate continuous wave (CW) lasers [14]. Moreover, the distinct linearity of the data points further validates the use of this approach for the examination of CW lasers.…”
Section: Determination Of Absorption Lengthmentioning
confidence: 99%
See 1 more Smart Citation